Business English instruction: Empowering learners with the 4Cs of the 21st century - Aben Ahmed, Mahdi (Frontiers in Education, 2022)
This study is a descriptive inquiry to explain how the 4Cs (communication, critical thinking, creativity, and collaboration) skills of the 21st century can be integrated into contemporary Business English instruction. The participants in the study are 140 Business English teachers at an academic institution in the eastern part of Saudi Arabia. The study is driven by the belief that educators in this field need to create modern language instruction involving the 21st century 4Cs: communication, collaboration, critical thinking, and creativity by the intervention of carefully planned objectives, varied activities, varieties of teaching methodologies, technological tools and materials, interaction patterns, teachers’ professional development and students’ awareness and cultural background. Using two questionnaires, the study gauged EFL teachers’ perceptions of the application of a specially developed 4Cs framework for Business English, to ensure that the students enrolled in these courses are fit to take on the role of global citizens. Findings show that teachers are positive about the appropriateness of applying the framework in the context of 21st century skills, and a viable degree of effectiveness in a learning environment. Participant teachers who applied this approach using the conceptualized paradigm in teaching Business English recommend its efficacy due to relevant pedagogical implications and practical principles that were discovered. The study concludes with six principles that can be directly used to ensure that the 4Cs which are a necessity in the 21st education system are integrated by educators in ELT instruction.